Rocket Observations of Plasma Irregularities in the Auroral Ionosphere - Hirotaka MORI; Tadahiko OGAWA; Shigeru MIYAZAKI (National Institute of Polar Research, 1979)
This paper reports the analytical results of electron density irregularities observed in the disturbed nighttime E-region by S-210JA-25, which was fired by the 17th Japanese Antarctic Research Expedition party. These irregularities were observed in the height range of 102-113 km by a Langmuir probe on board the rocket. It is found that the height variation of the frequency spectrum of the irregularities can be explained by theories of the cross-field and two-stream instabilities. However, the fact that the irregularities decayed abruptly above the height of 113 km is inconsistent with the theoretical prediction.